The Rise of For-Profit Higher Education: A General Equilibrium Analysis - Ciprian Domnisoru; Ioana Cosmina Schiopu (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The growth of for-profit colleges has been historically aided by online instruction, and budget crunches at public institutions, circumstances which have resurfaced during the COVID-19 pandemic. We set up and calibrate a general equilibrium model of competition between public and for-profit institutions in the U.S. four-year college market. Our predicted levels of tuition, instructional spending and average student body ability match data counterparts well. In policy experiments, we vary the generosity of public support for higher education and we consider the effects of “gainful employment” legislation that would link access to federal funding for universities to their graduates' debt-to-earnings ratios. We find that Pell Grant cap increases would benefit for-profit colleges, which flexibly decrease tuition and instructional spending to attract a higher number of low-income beneficiaries. Our simulations indicate for-profit colleges prefer to comply with gainful employment standards, but do so by lowering tuition and instructional quality.
Keywords: D40; D58; I28; 330; college choice; funding policies; non-traditional students; general equilibrium